ANALYSIS OF THE STATUS AND TRENDS DEVELOPMENT OF INDUSTRIAL INFRASTRUCTURE OF RUSSIAN INDUSTRY - Natalia V. Filimonova (Статистика и экономика)
The article presents the methodologicaland methodical bases of research analyzing the status and trends of developmentof industrial infrastructure of Russian industry. Focuses on the organizational side of the issue as the comparativecharacteristics. Isolated retrospectiveresearch approach. Considered sectoral,regional, national and international levelsof development of industrial infrastructure.